Gross Employment Effects in the Renewable Energy Industry in Germany : An Input–Output Analysis from 2000 to 2018 - Marlene O'Sullivan; Dietmar Edler (sustainability, 2020)
The purpose of this paper is to provide detailed insights into an approach to measure gross employment of the renewable energy (RES) industry in Germany in order to improve transparency and comparability. The method applied for the assessment of gross employment figures follows the input–output (IO) modeling approach and covers direct as well as indirect employment effects.All-in-all, four different approaches of applying the IO-methodology are described. The analysis includes11 different RES technologies. It provides information on employment in manufacturing and installation,operation and maintenance (O&M), as well as the provision of biogenic fuels. The results show the relevance of the manufacturing and installation sector as well as the influence of foreign trade on this sector. On the other hand, it reveals the growing importance of O&M as well as the provision of biogenic fuels and their role in providing a more stable development of employment in the RES industry. Our main methodological conclusions are as follows: (1) data availability is a major challenge in assessing employment effects of specific technologies; (2) there are many different ways to apply the IO-modeling approach to specific technologies and services; (3) the transfer of results to other countries is limited.
Keywords: 330; renewable energy; input-output analysis; gross employment; jobs; labor